2018
DOI: 10.1128/mbio.01932-18
|View full text |Cite
|
Sign up to set email alerts
|

RNA Viruses in Blechomonas (Trypanosomatidae) and Evolution of Leishmaniavirus

Abstract: Flagellates belonging to the genus Leishmania are important human parasites. Some strains of different Leishmania species harbor viruses (leishmaniaviruses), which facilitate metastatic spread of the parasites, thus aggravating the disease. Up until now, these viruses were known to be hosted only by Leishmania. Here, we analyzed viral distribution in Blechomonas, a related group of flagellates parasitizing fleas, and revealed that they also bear leishmaniaviruses. Our findings shed light on the entangled evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 78 publications
2
40
0
6
Order By: Relevance
“…Each contained a single ORF; 2012, 334, and 165 aa long in the L, M, and S fragments, respectively. As previously reported for other leishbunyaviruses [32], the proportions of particular viral segments were not even. As compared to the L RNA, the S segment was about six-fold more abundant ( Table 1 and Table S1).…”
Section: Viral Dsrna In Leishmania (M) Martiniquensissupporting
confidence: 48%
See 2 more Smart Citations
“…Each contained a single ORF; 2012, 334, and 165 aa long in the L, M, and S fragments, respectively. As previously reported for other leishbunyaviruses [32], the proportions of particular viral segments were not even. As compared to the L RNA, the S segment was about six-fold more abundant ( Table 1 and Table S1).…”
Section: Viral Dsrna In Leishmania (M) Martiniquensissupporting
confidence: 48%
“…The sequences of all three viral segments were complete and included both 5 and 3 terminal "panhandle" inverted repeats (5 -acacaaaga tctttgtgt-3 , Figure 2) necessary for replication, transcription, and translation in bunyaviruses [3]. The sequences of the identified terminal repeats were identical to those of other known LBVs [32,38].…”
Section: Viral Dsrna In Leishmania (M) Martiniquensismentioning
confidence: 93%
See 1 more Smart Citation
“…Due to the nature of the cloacal swabs, it is impossible to accurately determine the host for these viruses, although some information can be gleaned from the families in which these virus fall. For example, the Narnaviridae are known to infect fungi and protists, while the related Leviviridae infect bacteria [58][59][60][61]. Other novel viruses fell within invertebrate associated clades of the Nodaviridae and Tombusviridae, associated with both vertebrate and invertebrate infecting viruses in the Picornavirales [36].…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic tree revealed that many of the identified mycoviruses were originated from fungi; however, some mycoviruses had strong phylogenetic relationships with those from insects and plants. In particular, four known narnaviruses derived from trypanosomatids were closely related with those from insects and fungi, suggesting that the previously identified narnaviruses from insects might be derived from insect parasites (38). It is likely that the insect parasites were also included during RNA preparation from insect tissues.…”
Section: Discussionmentioning
confidence: 97%